Mediterranean diet adherence and risk of incident kidney stones. Issue 5 (9th April 2020) - Rodriguez, Adrian; Curhan, Gary C; Gambaro, Giovanni; Taylor, Eric N; Ferraro, Pietro Manuel
ABSTRACT: Background: Diet plays an important role in kidney stone formation. Several individual components have been associated with the risk of kidney stone formation, but there is limited evidence regarding the role of healthful dietary patterns. Objective: To prospectively study the association between adherence to the Mediterranean diet and the risk of incident kidney stones. Methods: We conducted a longitudinal study using 3 different cohorts: the Health Professionals Follow-up Study ( n = 42, 902 men), the Nurses' Health Study I ( n = 59, 994 women), and the Nurses' Health Study II ( n = 90, 631 women). We assessed diet every 4 y using an FFQ and calculated adherence to a Mediterranean diet using the alternate Mediterranean diet score (aMED). A subgroup of 6077 participants provided ≥1 24-h urine sample, and urinary solute excretion was analyzed. We used Cox proportional hazards regression to examine the independent association between the aMED and incidence of kidney stones, adjusting for potential confounders. We used adjusted linear regression models to study the relation between aMED and urine composition. Results: During 3, 316, 633 person-years of follow-up, 6576 cases of incident kidney stones were identified. For participants in the highest aMED score category, the risk of developing a kidney stone was between 13% and 41% lower compared with participants in the lowest score (pooled HR: 0.72, 95% CI: 0.59, 0.87; P value for trend <0.001). A higher aMED score was associated with higher urinary citrate, magnesium, oxalate, phosphate, uric acid, volume, and pH, and lower urinary sodium, resulting in lower supersaturation for calcium oxalate, calcium phosphate, and uric acid. Conclusion: Adherence to a Mediterranean diet is associated with a lower risk of developing a kidney stone. Abstract : Diet plays an important role in kidney stone formation. Several individual components have been associated with an increased or decreased risk of kidney stone formation, but there is limited evidence about the role of healthful dietary patterns, such as the Mediterranean diet (MD). Thus, in this article we aimed to study prospectively the association between adherence to the MD and the risk of incident kidney stones, using three large prospective cohorts. We also analyzed the data from 6, 077 participants who provided at least one 24-h urine sample. During the follow-up, 6, 576 cases of incident kidney stones were identified. For participants with the highest adherence to MD, the risk of developing a kidney stone was between 13% and 41% lower compared with participants in the lowest score in the cohorts. Higher MD adherence was also associated with a better urinary profile for kidney stone-forming patients.